Konstruksi Kesalahan Korporasi sebagai Arsitektur Perdagangan Satwa Liar Jaringan Transnasional Melalui Teori Psikopati - Ahmad Yusup (Jurnal Penelitian Hukum De Jure, 2026)
The illegal wildlife trade is transforming into a complex and organized form of transnational crime, no longer dominated by individual perpetrators, but increasingly involving corporations as strategic actors. This article analyzes how corporations play a role as the architecture of the transnational network wildlife trade and how psychopathic theories construct corporate wrongdoing in the domain. This research is designed with a type  of socio-legal research that not only uses the basis of legal theory approaches, but also combines it with the approaches of other disciplines, such as criminology and psychology. The results show that corporate involvement in transnational network wildlife trade is not incidental, but systematic and structured, utilizing legitimate business mechanisms to disguise its illegal activities. The findings of the study also confirm that psychopathic theory is relevant in explaining the construction of corporate wrongdoing that conducts the cross-border wildlife trade, such as the absence of empathy, the absence of guilt, and the absence of moral and social responsibility. Therefore, a complex criminal accountability approach is needed to address corporate crime in the domain, strengthened through the Mutual Legal Assistance (MLA) mechanism to overcome jurisdictional barriers and support cross-border evidence collection against corporations.